Using social media in teaching foreign languages - Shpenik Silvia; Spenik Szilvia („RIK-U” Kft., 2018)
Abstract. In the modern world, information and computer technologies are becoming increasingly important in teaching foreign languages. At the present stage, there is unlimited access to the Internet in time and space through an extensive network of mobile systems. All the above mentioned resulted in the transformation of the Internet into a mass communication medium, which can replace television, radio, interactive media (tape recorder, video player, etc.). Rapid technological development affects people’s everyday life, learning, giving rise to new habits, switching to online communication. This new way of self-expression is possible due to many social networks available through our mobile devices anywhere and anytime.
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: social media; teaching; foreign language